University students' metaverse attachment and its predictors: escaping from reality - Xu, Yan; Chen, Linmin (Frontiers in Psychology, 2025)
The most ambitious vision of metaverse technology is to create virtual spaces that offer possibilities equivalent to those in the real world. However, like any emerging technology, the metaverse has sparked controversies and raised questions. Why do individuals seek to migrate to the metaverse? Virtual reality experiences enable people to immerse themselves in virtual environments for hours, interacting with content within these worlds, thus forming another virtual universe—the metaverse—that provides a sense of place and alternative reality. As an emerging research domain, the metaverse holds great potential in offering an alternative habitat for individuals. While the significance of escapism in the metaverse has been discussed in existing literature, what drives university students to escape into the metaverse and its consequences remain unclear. In this study, we leverage Escape Theory to examine how various psychological challenges drive university students to escape reality through the metaverse and develop an attachment to this virtual place. We collected 585 responses from university students who are users of metaverse applications based on virtual reality. The data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. Our findings reveal that autonomy problems, study competence problems, relatedness problems, amount of time spent in the metaverse, and interactivity all contribute to university students engaging with the metaverse as a means of escaping reality, subsequently leading to virtual place attachment. This study contributes to metaverse literature by exploring the real-life challenges that may lead university students to engage in metaverse escapism. These results provide a deeper understanding of individuals' perceptions of the metaverse and how the connections between virtual and real spaces translate into attitudes toward metaverse technologies.